Development of Hydroxyapatite-Based Bioceramic Hardness Model Based on Variations in Synthesis Conditions - Fitri Afriani; Yuant Tiandho (Jurnal Inovasi Teknologi, 2020)
Hydroxyapatite is bioceramics which have conducive biocompatible property and have been widely used in bone scaffolds. Although they have potential development, there have not been any matematical model that elaborates the relation between the parameter of synthetic conditons and the mechanical properties of hydroxyapatite. That is why, this article tries to present the relation model between the hardness of hydroxyapatite based on variety of synthetic conditions and sintering temperature, relative density, and the size of particle as well. Developing hardness model is performed on the basis of its relation with the responses from each experiment factor. Validating model which was carried out through comparison between the model and the data of experiments indicates that the model proposed has a good accuracy and capable for explaining the bond between the parameter of synthetic and the hardness of hydroxyapatite.